Breathing Abnormalities During Sleep and Wakefulness in Rett Syndrome: Clinical Relevance and Paradoxical Relationship With Circulating Pro-oxidant Markers - Leoncini, Silvia; Signorini, Cinzia; Boasiako, Lidia; Scandurra, Valeria; Hayek, Joussef; Ciccoli, Lucia; Rossi, Marcello; Canitano, Roberto; De Felice, Claudio (Frontiers in Neurology, 2022)
Background: Breathing abnormalities are common in Rett syndrome (RTT), a pervasive neurodevelopmental disorder almost exclusively affecting females. and linked to mutations in the methyl-CpG-binding protein 2 (MeCP2) gene. Our aim was to assess the clinical relevance of apneas during the sleep-wakefulness cycle in an RTT population and their possible impact on circulating oxidative stress markers. Methods: Female patients with a clinical diagnosis of typical RTT (n=66), MECP2 gene mutation and clinical apneas were enrolled (mean age, 12.5 years). Baseline clinical severity, arterial blood gas analysis, and red blood cell count were assessed. Breathing monitoring was performed during the wakefulness and sleep states (average recording time:13 ± 0.5 h) by a portable polygraphic screening device. According to the prevalence of breath holdings, the population was categorized into wakefulness apneas (WA) and sleep apneas (SA), and the apnea-hypopnea index (AHI) was calculated. The impact of respiratory events on oxidative stress was assessed by plasma and intra-erythrocyte non-protein-bound iron (IE-NPBI and P-NPBI, respectively), and plasma F2-isoprostanes (F2-IsoPs) assays. Results: A significant prevalence of obstructive apneas with values of AHI > 15 was present in 69.7% of the RTT population. The SA group showed significantly increased AHI values > 15 (p=0.0032), total breath holding episodes (p=0.007), and average SpO2 (p=0.0001) as well as lower nadir SpO2 (p=0.0004) as compared with the WA patients. WA and SA patients’ sub-groups showed no significant differences in arterial blood gas analysis variables (p>0.089). Decreased red blood cell mean cell haemoglobin (MCH) (p=0.038) was observed in the WA group. P-NPBI levels were significantly higher in the WA as compared to the SA group (p = 0.0001). Stepwise multiple linear regression models showed WA being related to nadir SpO2, average SpO2, and P-NPBI (adjusted R2=0.613 multiple correlation coefficient = 0.795 p < 0.0001) with P-NPBI being related to average SpO2, blood PaCO2, red blood cell mean corpuscular volume (MCV), age, and topiramate (adjusted R2=0.551 multiple correlation coefficient = 0.765 p < 0.0001). Conclusions: Our findings indicate that the impact of apneas in RTT is uneven according to sleep-wakefulness cycle, with plasma redox active iron representing a potential novel therapeutic target.